2015
DOI: 10.1016/j.matchar.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural anomalies in hot-isostatic pressed U–10 wt.% Mo fuel plates with Zr diffusion barrier

Abstract: Microstructural anomalies in the co-rolled-and-HIP'ed U-10 wt.% Mo (U10Mo) metallic fuel plate with Zr diffusion barrier assembly were examined as a function of HIP temperature (from 520 to 580°C) and duration (45, 60, 90, 180 and 345 min) by scanning and transmission electron microscopy. The anomalies observed in this study are carbide/oxide inclusions within the U10Mo fuel alloy, and regions of limited interaction between the U10Mo alloy and Zr barrier, frequently associated with carbide/oxide inclusions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Based on literature, UC is known to have a face-centered cubic structure with four formula units per unit cell (eight atoms per unit cell) and the lattice parameter taken from literature was 4.96 angstroms (Rundle et al 1948, Austin 1959, Park et al 2015. Based on this, the volume per atom for UC phase was calculated to be 1.53 × 10 −29 m 3 .…”
Section: Step 2: Estimating Volume Of Uc and Umo Phase Per Atommentioning
confidence: 99%
See 1 more Smart Citation
“…Based on literature, UC is known to have a face-centered cubic structure with four formula units per unit cell (eight atoms per unit cell) and the lattice parameter taken from literature was 4.96 angstroms (Rundle et al 1948, Austin 1959, Park et al 2015. Based on this, the volume per atom for UC phase was calculated to be 1.53 × 10 −29 m 3 .…”
Section: Step 2: Estimating Volume Of Uc and Umo Phase Per Atommentioning
confidence: 99%
“…U-10Mo phase is known to have BCC structure with two atoms per unit cell, with a lattice parameter of 3.41 angstroms (Burkes et al 2009, Park et al 2015. Based on this, the volume per atom for UMo matrix phase was calculated to be 1.98 × 10 −29 m 3 .…”
Section: Step 2: Estimating Volume Of Uc and Umo Phase Per Atommentioning
confidence: 99%
“…The TEM samples were prepared by focused ion beam and an in-situ lift-out process was utilized for sample extraction (FIB-INLO; FEI™ TEM200) using site-specific capability. Typical phase constituents and microstructural developments due to interdiffusion and reaction at the U10Mo/Zr and Zr/AA6061 interfaces in these samples were reported previously [8,9]. This paper reports, in detail, the phase transformation of γ-phase in the U10Mo fuel alloy as functions of HIP temperature, holding time and ramping/cooling (H/C) rate as listed in Table 3.…”
Section: Methodsmentioning
confidence: 63%
“…A Zr diffusion barrier is typically placed between the U10Mo fuel alloy and Al-alloy cladding to prevent interaction between the fuel and cladding. Previously, microstructure resulting from the interdiffusion and solid-state reaction between different constituents of the fuel plate was reported [8][9][10][11][12][13]. In addition, within the fuel alloy, Meyer et al [11] reported the presence of "chemical banding" with inhomogeneous Mo content within the fuel alloy, and Jue et al [12] identified γ-phase decomposed regions consisting of α and γ' phases due to heat treatment near the eutectoid temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on how a fuel plate is fabricated, it is possible for the U-10Mo alloy fuel microstructure to consist of elongated fuel grains in the rolling direction, areas of transformed c-(U,Mo) phase, areas of chemical banding, and impurity phases in different areas of the microstructure. 3,[10][11][12] Figure 1 shows examples of these microstructural features. The elongated grains results from the rolling process.…”
Section: As-fabricated Microstructures U-10mo Alloymentioning
confidence: 99%